Bartleby à Belleville, ou quand les Malaussène invitent Isaac Sidel : le crossover fraternel de Daniel Pennac (Des chrétiens et des Maures) et Jerome Charyn (Appelez-moi Malaussène) - Sophie Vallas (Transatlantica)
In 1996 Daniel Pennac published a brief novel entitled Des chrétiens et des Maures, a reference to one of the latino specialties Jerome Charyn’s famous commish, Isaac Sidel, is especially fond of ("Cristianos y Moros"). Sidel meets the famous Malaussène family in Paris and finds a most necessary shelter in a violent Belleville. In 1998, Charyn went on with this crossover between Pennac’s noir universe and his in Appelez-moi Malaussène (never published in English) : Sidel goes back to Paris and discovers he is the father of one of the Malaussène children. "Bartleby the Scrivener" is the intertext that both authors draw on in order to twin their respective sagas : Melville’s tale allows them to weave their long-standing meditations on the issues of originality, identity, name, noire paternity and fictional fraternity.